SISTEM PENDUKUNG KEPUTUSAN MENENTUKAN KENAIKAN KELAS DENGAN MENGGUNAKAN METODE TOPSIS PADA SMK YAPIM MABAR - Priantoni Hia; Hardianto Hardianto; Ratih Adinda Destari (Universitas Raharja, 2018)
The most important decision-making in schools is class decision making. The old way with the manual system can lead to slow decision-making. This is of course caused by a very basic problem, namely the decision-making is not appropriate. Therefore a decision support system is needed that can help the teacher to determine the class increase. The design of decision support system in this study aims to apply the application to determine the increase of class, To overcome the problem, required a decision support system of computerized class increase which later can produce quality decisions that can process data and student values ​​effectively and efficiently and can measure the ability of students both academically and non academic so that activities that have been done manually can be done using the computer and mistakes in decision-making class increase can be avoided as well as time in determining decision-making class increase much faster and effective. Decision support system is designed using visual basic programming languages ​​2010 and SQL Server 2008. The process in this study using Topsis method.